Research progress on the physiological, biochemical and molecular regulatory mechanisms of fruit tree responses to high-temperature stress - Que Wang; Yaqiong Wu; Wenlong Wu; Lianfei Lyu; Weilin Li (Horticultural Plant Journal)
Fruit trees face various adverse environmental factors, such as extreme hydrothermal changes, soil salinization and low precipitation, leading to different types of stress. High temperature is one of the main factors affecting the growth of fruit trees, and an appropriate ambient temperature is a necessary condition for the normal growth and development of fruit trees. Since the 20th century, due to the intensification of the greenhouse effect and global warming, there has been a significant increase in the occurrence and duration of extreme hot weather in summer has been occurring frequently and for longer durations. Thus, the growth and production of fruit trees are affected by severe high-temperature stress. Therefore, this paper primarily summarized the impacts of high-temperature stress on fruit growth and development, flowering, fruiting, fruit setting and quality. It also discussed the physiological and biochemical responses of fruit trees to high-temperature stress, research progress on the molecular mechanisms and signal transduction pathways underlying fruit tree resistance to heat or high temperature, and research on the investigation of relevant metabolites of fruit trees under stress conditions. The future research directions were discussed, and prospects and potential difficulties were proposed to serve a reference for further investigation on the high-temperature tolerance of fruit trees.